Anti (Q, L)-Fuzzy Subhemirings of a Hemiring - LATHA, M; ANITHA, N (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, an attempt has been made to study the algebraic nature of an anti (Q, L)-fuzzy subhemirings of a hemi ring.